The Use Of Puzzle Media In Improving The Mathematical Ability Of Children With Mild Mental Disabilities - Firma, Destiani; Astuti, Eka Yuli (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to describe the use of puzzle media in improving the arithmetic skills of mildly mentally disabled third-grade students at SLB BC Bina Mandiri Garut. The background of this study focuses on the need for mildly mentally disabled children to have concrete learning media that suits their characteristics, especially in understanding basic mathematics. The method used was qualitative descriptive, while data collection techniques were conducted through observation, interviews, and documentation. The results of the study indicate that puzzle media can enhance children's attention and learning motivation, although there are some challenges such as limitations in fine motor skills and difficulty in understanding instructions. Teachers addressed these challenges by providing intensive guidance, modifying the media, and implementing positive reinforcement strategies. This study contributes to the development of adaptive learning in special education.